2022
DOI: 10.1002/er.7818
|View full text |Cite
|
Sign up to set email alerts
|

Co/Zn‐based bimetallic MOF ‐derived hierarchical porous Co/C composite as cathode material for high‐performance lithium‐air batteries

Abstract: Structural optimization and electrocatalyst utilization in air cathodes have been identified as two major factors affecting the overall performance of a lithium-air battery. Herein, a cobalt@porous carbon composite, Co@C (700-1000) was obtained by facile annealing of a Co/Zn-bimetallic metalorganic framework (MOF). In the Co/Zn-MOF, cobalt cluster was used as a precursor of the catalyst and zinc cluster as a sacrificial template to generate meso-and macropores. The lithium-air battery with the assembled Co@C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In addition, two accompanying satellite peaks for the Mn 2p orbit are at positions 655.7 and 643.3 eV. The Zn 2p spectra (Figure b) clearly show Zn 2p 1/2 at 1044.3 eV and Zn 2p 3/2 at 1020.5 eV . The above results show that Zn and Mn elements exist in ZnMn-SQ in the form of bivalent.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, two accompanying satellite peaks for the Mn 2p orbit are at positions 655.7 and 643.3 eV. The Zn 2p spectra (Figure b) clearly show Zn 2p 1/2 at 1044.3 eV and Zn 2p 3/2 at 1020.5 eV . The above results show that Zn and Mn elements exist in ZnMn-SQ in the form of bivalent.…”
Section: Resultsmentioning
confidence: 59%
“…The peaks located at 652.7 and 640.4 eV in the XPS spectrum of Mn 2p correspond to Mn 2p 1/2 and Mn 2p 3/2 , respectively. 40 In addition, two accompanying satellite peaks for the Mn 2p orbit are at positions 655.7 and 643.3 eV. The Zn 2p spectra (Figure 2b) clearly show Zn 2p 1/2 at 1044.3 eV and Zn 2p 3/2 at 1020.5 eV.…”
Section: Synthesis and Characterizationmentioning
confidence: 89%
“…It has been found that all the negative electrodes show typical type IV adsorption-desorption isotherms with an H3 type hysteresis loops within the P/P o range 0.5-1.0 relative pressure, indicating the presence of abundant mesopores (shown in Figure 1h). [38,39] As the amount of Zn increases, the hysteresis loop gets larger indicating, more mesopores formation after the addition of Zn, which leads to increase in the Brunauer-Emmett-Teller (BET) specific surface area (SSA). The SSA was found in increasing order of 128.04, 143.27, 157.30, and 160.71 m 2 g −1 for Co-NP@MX/CF, Co-N/C 0.25 @MX/CF Co-N/C 0.5 @MX/CF, and optimized Co-N/C 1 @MX/CF, respectively.…”
Section: Physical Characterization Of Co-n/c@mx/cf Electrodementioning
confidence: 99%
“…Mesoporous cathodes with a high pore volume have been found to promote O 2 diffusion and improve specific capacity in lithium-air batteries. [25,26] Additionally, the use of non-conductive binders in preparing electrodes with active materials of particle morphology leads to the formation of inactive regions, resulting in non-uniform deposition of discharge products. Therefore, the consistency and continuity of the electrons and ions conductivity of the air cathode is crucial for the homogeneous distribution of discharge products.…”
Section: Introductionmentioning
confidence: 99%